Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Let's solve the given expression step-by-step. The expression is:
[tex]\[ \left(\frac{(\sqrt{m}+n)^2}{2}\right) (3 p) \][/tex]
Given the values [tex]\( m = 4 \)[/tex], [tex]\( n = 2 \)[/tex], and [tex]\( p = 3 \)[/tex]:
1. Calculate the square root of [tex]\( m \)[/tex]:
[tex]\[ \sqrt{m} = \sqrt{4} = 2 \][/tex]
2. Add [tex]\( n \)[/tex] to the square root of [tex]\( m \)[/tex]:
[tex]\[ \sqrt{m} + n = 2 + 2 = 4 \][/tex]
3. Square the resulting sum:
[tex]\[ (\sqrt{m} + n)^2 = 4^2 = 16 \][/tex]
4. Divide the squared result by 2:
[tex]\[ \frac{(\sqrt{m} + n)^2}{2} = \frac{16}{2} = 8 \][/tex]
5. Multiply the result by [tex]\( 3p \)[/tex]:
[tex]\[ \left( \frac{(\sqrt{m} + n)^2}{2} \right)(3p) = 8 \cdot (3 \times 3) = 8 \cdot 9 = 72 \][/tex]
Thus, the final result of the given expression is:
[tex]\[ 72 \][/tex]
Additionally, the intermediate results are:
[tex]\[ \sqrt{m} + n = 4, \quad (\sqrt{m} + n)^2 = 16, \quad \frac{(\sqrt{m} + n)^2}{2} = 8, \quad \text{and} \quad \left(\frac{(\sqrt{m}+n)^2}{2}\right)(3p) = 72. \][/tex]
[tex]\[ \left(\frac{(\sqrt{m}+n)^2}{2}\right) (3 p) \][/tex]
Given the values [tex]\( m = 4 \)[/tex], [tex]\( n = 2 \)[/tex], and [tex]\( p = 3 \)[/tex]:
1. Calculate the square root of [tex]\( m \)[/tex]:
[tex]\[ \sqrt{m} = \sqrt{4} = 2 \][/tex]
2. Add [tex]\( n \)[/tex] to the square root of [tex]\( m \)[/tex]:
[tex]\[ \sqrt{m} + n = 2 + 2 = 4 \][/tex]
3. Square the resulting sum:
[tex]\[ (\sqrt{m} + n)^2 = 4^2 = 16 \][/tex]
4. Divide the squared result by 2:
[tex]\[ \frac{(\sqrt{m} + n)^2}{2} = \frac{16}{2} = 8 \][/tex]
5. Multiply the result by [tex]\( 3p \)[/tex]:
[tex]\[ \left( \frac{(\sqrt{m} + n)^2}{2} \right)(3p) = 8 \cdot (3 \times 3) = 8 \cdot 9 = 72 \][/tex]
Thus, the final result of the given expression is:
[tex]\[ 72 \][/tex]
Additionally, the intermediate results are:
[tex]\[ \sqrt{m} + n = 4, \quad (\sqrt{m} + n)^2 = 16, \quad \frac{(\sqrt{m} + n)^2}{2} = 8, \quad \text{and} \quad \left(\frac{(\sqrt{m}+n)^2}{2}\right)(3p) = 72. \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.